Moina hemanti sp. nov., a new species of the genus Moina s.l. (Branchiopoda: Anomopoda) from Pune, India - Padhye, Sameer M; Dumont, Henri J (Zootaxa, 2014)
We describe and figure Moina hemanti sp. nov. from ephemeral pools on the campus of Pune University, India. Although the pools flood during the monsoon, the moinid only appears irregularly and for a short period of time. In morphology, it is extremely close to Moina dumonti from Mexico and Cuba. This geographic gap remains unexplained for the time being, although more similar cases among cladocerans are on record. Molecular analysis has suggested that M. hemanti is relatively close to Moinodaphnia, and might form a genus in its own right, presumably together with M. dumonti. The latter, however, remains to be analyzed. Further candidates for this clade are Moina oryzae and M. rostrata, if the presence of an ocellus and/or a rostrum can be shown to be apomorphies.